'Real‐world' compensatory behaviour with low nicotine concentration e‐liquid: subjective effects and nicotine, acrolein and formaldehyde exposure. (19th June 2018) - Dawkins, Lynne; Cox, Sharon; Goniewicz, Maciej; McRobbie, Hayden; Kimber, Catherine; Doig, Mira; Kośmider, Leon
Abstract: Aims: To compare the effects of (i) high versus low nicotine concentration e‐liquid, (ii) fixed versus adjustable power and (iii) the interaction between the two on: (a) vaping behaviour, (b) subjective effects, (c) nicotine intake and (d) exposure to acrolein and formaldehyde in e‐cigarette users vaping in their everyday setting. Design: Counterbalanced, repeated measures with four conditions: (i) low nicotine (6 mg/ml)/fixed power; (ii) low nicotine/adjustable power; (iii) high nicotine (18 mg/ml)/fixed power; and (iv) high nicotine/adjustable power. Setting: London and the South East, England. Participants: Twenty experienced e‐cigarette users (recruited between September 2016 and February 2017) vaped ad libitum using an eVic Supreme™ with a 'Nautilus Aspire' tank over 4 weeks (1 week per condition). Measurements: Puffing patterns [daily puff number (PN), puff duration (PD), interpuff interval (IPI)], ml of e‐liquid consumed, changes to power (where permitted) and subjective effects (urge to vape, nicotine withdrawal symptoms) were measured in each condition. Nicotine intake was measured via salivary cotinine. 3‐Hydroxypropylmercapturic acid (3‐HPMA), a metabolite of the toxicant acrolein, and formate, a metabolite of the carcinogen formaldehyde, were measured in urine. Findings: There was a significant nicotine concentration × power interaction for PD ( P  < 0.01). PD was longer with low nicotine/fixed power compared with (i) high nicotine/fixed power ( P  < 0.001) and (ii) low nicotine/adjustable power ( P  < 0.01). PN and liquid consumed were higher in the low versus high nicotine condition (main effect of nicotine, P  < 0.05). Urge to vape and withdrawal symptoms were lower, and nicotine intake was higher, in the high nicotine condition (main effects of nicotine: P  < 0.01). While acrolein levels did not differ, there was a significant nicotine × power interaction for formaldehyde ( P  < 0.05). Conclusions: Use of a lower nicotine concentration e‐liquid may be associated with compensatory behaviour (e.g. higher number and duration of puffs) and increases in negative affect, urge to vape and formaldehyde exposure.